PERUBAHAN MAKNA PADA PERCAKAPAN SIMPATISAN CAPRES-CAWAPRES 2024 DI MEDIA SOSIAL - Ulfa Zakaria (Cross-border, 2024)
The democracy party is a 5-year event in the election of the president and vice president, but the supporters have a uniqueness in conveying opinions through various languages and meanings used, so it is interesting to analyze, The study aims to see how the meaning changes in the conversations of sympathizers of the 2024 presidential candidates on social media. This research is qualitative with descriptive analysis with data sources from various research results throughout Indonesia. The results of research on several journal analyses that have been published that social media is very effective in the use of language and meaning conveyed by sympathizers of the vice president and vice president. So it needs to be re-examined that the language used according to the language comes from sympathizers, be it regional or Indonesian.